A STUDY ON THE STANDARDIZATION PARAMETERS OF CASSIA ANGUSTIFOLIA - Khare, Pragati; Kishore, Kamal; Sharma, Dinesh Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Now-a-days, the herbal medicines are much efficient for the treatment of various disorders as they have minimal side effects in comparison to the allopathic medicines. Cassia angustifolia, commonly called Senna belongs to the family Leguminosae and is a well-known laxative throughout the world. Senna is mostly found in Tirunelveli, Madurai, and Ramnathpuram districts of Tamil Nadu. Carbohydrates, tannins, alkaloids, flavonoids, and amino acid are the important chemical constituents of C. angustifolia. The objectives of the present study are to investigate various pharmacognostic, phytochemical analysis, and pharmacological properties of C. angustifolia. Methods: The powdered drug was used for estimating the loss on drying, ash values, fluorescence studies, chemical tests, and extractive values. Macroscopic and microscopic studies were also performed. Results: The transverse section (T.S). of leaf showed isobilateral structure along with paracytic stomata, nonlignified unicellular trichomes with warty walls, and fibrovascular bundle. The fluorescence characteristics of leaf powder were studied both in visible light and ultraviolet (UV) light (254 nm and 365 nm) after treatment with various reagents. Senna is composed of carbohydrates, tannins, alkaloids, flavonoids, and amino acid. It was reported that the total ash value was 11.23±0.25 w/w. The acid insoluble ash value was 1.4±0.1% w/w. Water soluble, ethanol, methanol, petroleum ether, and chloroform extractive values were 16.6±0.26% w/w, 3.7±1.75% w/w, 0.83±0.05% w/w, 1.6±0.1% w/w, and 3.2±0.25% w/w, respectively. Conclusion: The main pharmacological activities of Bauhinia variegata are anthelmintic, antiulcer, antitumor, antimicrobial, antidiabetic, anti-inflammatory, antigoitrogenic, and hepatoprotective. The present investigation provides the information on its pharmacognostic, phytochemical analysis, and pharmacological properties.